IMPLEMENTASI BUDAYA KESELAMATAN PASIEN PADA PERAWAT RAWAT INAP DI RUMAH SAKIT X KOTA SEMARANG - Lutfiyah Rizqulloh; Mugiyanto; Diah Kari Artati (LPPM Universitas Awal Bros, 2026)
Patient safety is an important component in improving the quality of healthcare services in hospitals. However, various patient safety incidents such as Adverse Events (AE), Near Misses (NM), and Non-Injury Events (NIE) still occur in various healthcare facilities, including Hospital X in Semarang City. This study aims to analyse the factors that influence patient safety culture among inpatient nurses at Hospital X in Semarang City. The study uses a quantitative design with a cross-sectional approach. The study population consists of all 442 inpatient nurses, with a sample of 82 respondents selected using simple random sampling. Data were collected via questionnaires and analysed using statistical tests to assess relationships among variables. The results showed that the average positive response to patient safety culture was 83.5%. The dimension with the highest positive response was cooperation within the unit (90.2%), followed by open communication and staffing, each at 84.1%. Bivariate analysis showed that all variables studied had a significant relationship with patient safety culture (p < 0.05), namely management support (p=0.018), cooperation within the unit (p=0.039), open communication (p=0.001), safety promotion by leaders (p=0.025), staffing (p=0.001), continuous improvement (p=0.011), patient safety perception (p=0.004), and non-punitive response to errors (p=0.007). The conclusion of the study shows that the patient safety culture at Hospital X in Semarang City is relatively good, but still needs to be strengthened, especially in terms of open communication and adequate staffing. The hospital is advised to increase management support, strengthen the incident reporting system without blaming, and optimise the number and distribution of health workers to improve patient safety.